Families and Technology (National Symposium on Family Issues,, 2018)
This timely reference takes a rigorous look at the myriad ways technology, from smartphones to dating apps to social media, is affecting family life and opening new areas for study. The book features cross-disciplinary perspectives on current trends in the role of technology in couple and family contexts. It focuses on the roles of parents in monitoring children's screen time, of technology in relationship formation, and of technology in changing family dynamics. Nuanced coverage considers the emerging conflicts and paradoxes associated with digital family life-closeness versus isolation, children versus parents as experts, and privacy versus surveillance. Contributors also identify new research opportunities as family roles and structures continue to evolve and technology becomes a greater lens for family studies. Among the topics covered: How parents manage young children's mobile media use Adolescents as the family technology innovators Online dating: changing intimacy one swipe at a time Technology in relational systems: roles, rules, and boundaries Television "effects" on international family change Interplay between families and technology: future investigations Families and Technology is a valuable resource for researchers and students in the fields of family studies, sociology, marriage and family therapy, social welfare, public health, and psychology. The book also appeals to policymakers and human services personnel dedicated to better understanding the impact of rapidly spreading technologies on families around the globe.